The gut microbiota‐derived metabolite indole‐3‐propionic acid enhances leptin sensitivity by targeting STAT3 against diet‐induced obesity - Zhiwei Wang; Shaying Yang; Liangju Liu; Aiqin Mao; Hao Kan; Fan Yu; Xin Ma; Lei Feng; Tingting Zhou (Clinical and Translational Medicine)
Abstract Obesity is associated with the gut microbiome. Here, we report that gut commensal Clostridia bacteria regulate host energy balance through the tryptophan‐derived metabolite indole‐3‐propionic acid (IPA). IPA acts as an endogenous leptin sensitiser to counteract obesity. Mechanistically, IPA is secreted from the gut into the circulation, and then targets to the STAT3 in the hypothalamic appetite regulation centre, promoting its phosphorylation and nuclear translocation, which enhances the body's response to leptin, and regulates the balance between appetite and energy metabolism. The in vitro pull‐down assays involving site‐directed mutagenesis demonstrate that Trp623 in the SH2 domain is the key binding site for STAT3‐IPA interaction. High‐fat diet (HFD), rather than genetic factors, induces excessive secretion of antimicrobial peptides by Paneth cells, inhibiting the growth of Clostridia in the gut and resulting in decreased production of the beneficial metabolite IPA. IPA or Clostridium sporogenes supplement effectively controls weight gain, improves glucose metabolism, and reduces inflammation in DIO mice. IPA fails to achieve such effects in ob/ob mice, while exogenous leptin administration restores the therapeutic effect of IPA. Our study suggests that the IPA‐based gut‐brain axis regulates host metabolism, and supplementation with microbiome‐derived IPA could be a promising intervention strategy for treating obesity.